La generación de valor agregado en la cadena de miel de Costa Rica - Parada Gómez, Alvaro Martín (2017)
Honey is a widely consumed product in the world and is produced intensively in countries such as China, Argentina, Mexico and Germany with a clear competitive advantage. China's leadership in world honey production is evident in the world supply. The level of world production in this country amounted to 450,300.0 metric tons in 2013 and supplies countries that are producers with insufficient supply, such as Spain, the United States and European Union countries, but with large consumer markets, but with large consumer markets. In Latin America, Brazil and Mexico are leading countries in the world supply of honey, producing 56,370 tons and 36,301 tons, respectively, in 2013. In the case of Costa Rica, the country has a significant supply, amounting to 1,150.0 metric tons in 2013; however, it is not comparable to the supply of the world's main with the supply of the main world leaders, but the quality of Costa Rican honey is high in great demand in the domestic market.